Should Auditors Report on Environmental Issues That Could Affect The Society - Rizal Yaya (Universitas Muhammadiyah Yogyakarta, Indonesia, 2002)
This study evaluates critically whether auditors should report the environmental issues that could affect the company. Therefore it is expected from this study to overcome an adequate argument on the issues regarding to the necessity to report the environmental issues of a client’s company by the auditor. This study indicate according to legal perspective it is accepted if auditors do not report it even though they know about the company’s disorder actions related to the environment. On the other hand, Islam encourages auditors to uncover such harmful actions, as it is mandatory to mankind especially those who have given knowledge about it (auditing) to protect environment and society. This duty is part of men’s accountability to Allah as the vicegerents on the earth.